El comercio informal y su legalización en el ministerio de inclusión económica y social, de la ciudad de Guaranda provincia Bolívar en el año 2010. - Guachilema Toapanta, Maria Angelica (2010)
The issue included "Informal Trade and its legalization in the Ministry of Economic and Social Inclusion, City Guaranda Bolivar Province in 2010." Trade is a means of survival for families guarandeñas not have a stable job. In practice, given the poverty in the city, it seems that many of the informal have no possibility of access to the execution, and then the ordinance truly becomes an attack against labor. The objective of this work is to design a legalization plan that will suit the needs of the informal trader because they are people who because of their socio-economic gaps seek, in the informal economy, a place to raise their families, if such Anything is possible with such low incomes. This research is due to the problem of informal trade because the state does not care about creating microenterprises in different cities and even worse in ours. Therefore this research work is of vital importance not only for the institution but also to society as the benefits that would provide them is implemented and will result legalized associations layers to be competitive. The reference framework has several aspects that transcend trade from origin, importance and different types of marketing, rating also lies in the differences between the informal and formal trade trade advantages and weaknesses, hence the importance it represents legalization. The methodology begins at the scene of events maintaining direct contact with those who are the managers of the research problem also applies where data are properly analyzed with input from existing bibliographies. Among the techniques used in this research are the interview addressed to the mayor the same that allowed us to discover important opinions and criteria, also compiled surveys of the institution and others aimed to capture data for our research field aimed different people. Within the proposed legalization plan for informal traders is the starting small association to facilitate the increase in same and have thus economic stability and a decent life.